2003
DOI: 10.1021/ma025713b
|View full text |Cite
|
Sign up to set email alerts
|

Direct ESR Detection of Free Radicals in the RAFT Polymerization of Styrene

Abstract: Benzyl (diethoxyphosphoryl)dithioformate (1) has been used to control the AIBN initiated radical polymerization of styrene. In a comparative study with the more popular RAFT transfer agent benzyl dithiobenzoate (2), compound 1 led to higher molecular weight polymers, although with a slightly worse polydispersity. During the polymerization process mediated by 1 a few radicals have been intercepted and characterized by means of ESR spectroscopy. The nature and relative amount of the various radical species varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 23 publications
2
47
0
Order By: Relevance
“…The intermediates have been observed directly by EPR in RAFT polymerizations of styrene and acrylate esters and in model reactions with dithiobenzoate and dithiophosphonate RAFT agents. [112,[131][132][133][134][135][136] The intermediates 3 or 5 are not detectable during MMA polymerizations or in polymerizations with aliphatic dithioester, trithiocarbonate, xanthate, or dithiocarbamate RAFT agents. This is attributed to the greater rate of fragmentation and the correspondingly shorter lifetime of the adduct in these polymerizations.…”
Section: Evidence In Support Of the Raft Mechanismmentioning
confidence: 99%
“…The intermediates have been observed directly by EPR in RAFT polymerizations of styrene and acrylate esters and in model reactions with dithiobenzoate and dithiophosphonate RAFT agents. [112,[131][132][133][134][135][136] The intermediates 3 or 5 are not detectable during MMA polymerizations or in polymerizations with aliphatic dithioester, trithiocarbonate, xanthate, or dithiocarbamate RAFT agents. This is attributed to the greater rate of fragmentation and the correspondingly shorter lifetime of the adduct in these polymerizations.…”
Section: Evidence In Support Of the Raft Mechanismmentioning
confidence: 99%
“…[2,3,5] The inclusion of chain-length dependence allows proper description of the initialization processes, but it omits the contribution of the very high intermediate radical concentration that the model predicts for RAFT-mediated reactions, which differs substantially from the experimentally observed values. [6][7][8] The possibility of these radicals being present as reversibly terminated species [9] is potentially a solution to this dilemma, but then the problem is closely related to the perceived flaw of the IRT model in that the concentrations of species that would be expected are such that experimental observation should be possible. In much the same fashion as the SF model, a number of groups have published data and explained their results using the IRT model.…”
Section: Introductionmentioning
confidence: 99%
“…The computed value of conversion (ca. 10%) was lower than the experimental one [12]. Conversely, the optimized model reproduced very well the consumption of BnSC(S)P(O)(OEt) 2 (5; Fig.…”
mentioning
confidence: 62%
“…20%. We also found that the ESR-spectral pattern of the system changed drastically during the first hour, and the reproduction of the spectra at different times by assuming the simultaneous presence of variable amounts of the four radicals 6 -9 (see Scheme 3) allowed the determination of the time profiles of their concentration [12].…”
mentioning
confidence: 74%
See 1 more Smart Citation